ROLE AND IMPORTANCE OF STHIRA BINDU (FIXED POINT) IN YOGA PHILOSOPHY - Subedi, K.; Panthi, D.; Jha, K.; Bhatta, C.R. (International Journal of Research -GRANTHAALAYAH, 2021)
It is true that all living things and all the mechanisms of entire universe are guided by mathematical relations and results. The theory of fixed point is one of the most leading gears of modern mathematics and its results are the most generally useful in mathematics which gives the solution of non-linear problems of various fields of modern subjects [9]. Also, the human brain can perform the intellectual courses that still have not been performed by digital computers. It may therefore be seen that quantum mechanics is very much associated with the consciousness of mankind [21]. Yoga is one of the few ways to understand the eventual reality mentioned in Vedanta, quantum physics and mathematics as well [19]. This paper investigates the role and importance of fixed point in eastern philosophies especially with yoga along with meditation focusing that mathematics plays a significant role in yoga philosophy.